2011
DOI: 10.5194/ms-2-157-2011
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Inventory of platforms towards the design of a statically balanced six degrees of freedom compliant precision stage

Abstract: Abstract. For many applications in precision engineering, a six degrees of freedom (DoF) compliant stage (CS) with zero stiffness is desirable, to deal with problems like backlash, friction, lubrication, and at the same time, reduce the actuation force. To this end, the compliant stage (also known as compliant mechanism) can be statically balanced with a stiffness compensation mechanism, to compensate the energy stored in the compliant parts, resulting in a statically balanced compliant stage (SBCS). Staticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Kim [8] developed a 3-DOF out-of-plane positioning stage for optical instrument alignment. As for 6-DOF stage, parallel mechanisms with six legs were extensively applied [9,10]. Recently, the hybrid serial-parallel flexure-based mechanisms are increasingly applied due to their special merits.…”
Section: Introductionmentioning
confidence: 99%
“…Kim [8] developed a 3-DOF out-of-plane positioning stage for optical instrument alignment. As for 6-DOF stage, parallel mechanisms with six legs were extensively applied [9,10]. Recently, the hybrid serial-parallel flexure-based mechanisms are increasingly applied due to their special merits.…”
Section: Introductionmentioning
confidence: 99%
“…With their distributed compliance they have a larger twist angle than hinges with concentrated compliance (e.g. notch joints) (Dunning et al 2011). To allow rotations with hinges based on leaf springs there are different possibilities as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Bistable compliant mechanisms have been an interesting mechanism with nonlinear stiffness behavior (Jensen et al, 2001;Hartono, 2001;Qiu et al, 2004;Li and Zhou, 2005;Sönmez, 2008; Todd et al, 2010). It has been shown that these mechanisms have the largest ratios of both compensated force and statically balanced stroke relative to the size (Dunning et al, 2011). A typical force-displacement curve of such a mechanism is shown in Fig.…”
Section: Statically Balanced Compliant Graspermentioning
confidence: 99%
“…However, all aforementioned works rely on preloading in a direction perpendicular to instrument actuation, and therefore protrudes outside the grasper and is difficult to be tuned for fabrication errors and improved performance. Collinear preloading has only been introduced in a few studies for other applications, such as: human skeleton (Chen and Zhang, 2011), MEMS (Tolou et al, 2010b) and precision stages (Dunning et al, 2011). This article presents a laparoscopic 2DoFs robotic arm with a statically balanced fully compliant laparoscopic grasper (namely SBCG) as the end effector.…”
Section: Introductionmentioning
confidence: 99%